Formation of the Kazakh Employees in the Conditions of Russian Management Military-Administrative Model - Aitmuhambetov, Aidar; Bekmagambetov, Ruslan K.; Bimoldanova, Aigul A.; Bekmagambetova, Maissara (Bylye Gody, 2017)
In article is considered as in the second half of the XIXth century in Kazakhstan professional groups of the Kazakh employees educated according to Russian-educational standards who had essential differences from other representatives of the Kazakh society are actually formed. Administrative-territorial and social-economic changes in the region persistently dictated need of formation of the specialists demanded by time from the local ethnic environment. The development of state-secular model of education is a consequence of this social factor. The Kazakh aristocracy was a basis of formation of employees group. It is distinguished several aristocratic clans oriented on innovative perceptions and further incorporation with new structure of management: Seydalin, Dzhanturin, Temirov, Nuralikhanov, Valikhanov, Ablaykhanov, Taukin, Babadzhanov, Karatayev, Sultangazin and others. The natives of sultan and other notable surnames of Younger and Central zhuz under the influence of the parents made a conscious choice in benefit of the military schools which educational status defined in prospect their inclusion in the rank military titulatura dominating in empires. The most of the Kazakh officers graduated from the Omsk and Orenburg military schools. Some Kazakh managers didn’t have corresponding military and civil education, but by the nature of a post had military ranks. In the XIXth century by virtue of the political situation which developed in Kazakhstan national and Russian officials mainly had military ranks. In administrative managerial hierarchy of the Kazakh employees remained the rank titulatura with the corresponding assignment of the military ranks emphasizing recognition of merits by the imperial government.
Keywords: the Russian state; imperial institutes; civil servants; Kazakh officials; military school; the district authority; Kazakh aristocracy; officers – sultans; soldiery ranks; reforms